2013
DOI: 10.1111/ane.12123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biomarker assessment of demyelinating events suggesting multiple sclerosis

Abstract: An extensive diagnostic evaluation of patients with an IDE is worthwhile to make prognostic predictions. More robust molecular biomarkers are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
5
0
3
Order By: Relevance
“…A correlation between CSF tau and progression of disability in MS patients has been shown only in one 3-year follow-up study [110]. In a small group of patients with CIS and clinically definite MS, investigated either at the acute attack (i.e., within 30 days) or several weeks or months later, our group found values of tau within normal limits [123], a finding that we later confirmed in a larger mostly independent cohort of CIS patients [73]. Interestingly, it has been shown that CSF tau levels decrease during the course of MS, as a likely effect of progressive parenchymal brain loss, hence, showing a negative correlation with clinical severity [124].…”
Section: Csf Markers Of Progressionsupporting
confidence: 59%
See 1 more Smart Citation
“…A correlation between CSF tau and progression of disability in MS patients has been shown only in one 3-year follow-up study [110]. In a small group of patients with CIS and clinically definite MS, investigated either at the acute attack (i.e., within 30 days) or several weeks or months later, our group found values of tau within normal limits [123], a finding that we later confirmed in a larger mostly independent cohort of CIS patients [73]. Interestingly, it has been shown that CSF tau levels decrease during the course of MS, as a likely effect of progressive parenchymal brain loss, hence, showing a negative correlation with clinical severity [124].…”
Section: Csf Markers Of Progressionsupporting
confidence: 59%
“…Clinical predictors of long-term disability in MS include male gender, older age, multifocal symptoms, efferent systems involvement, incomplete remission of the initial event, a short interval to the second event, and high relapse rate in the first 2–5 years after onset, although not all studies replicated the same findings (Table 1) [2427, 30, 31, 48, 73]. One single study reported a shorter time to secondary progressive MS in patients with family history of MS [74].…”
Section: Clinical and Paraclinical Markers Of Disability Progressionmentioning
confidence: 99%
“…10 Outros trabalhos já tinham demonstrado anteriormente que um maior número de lesões estava associado a uma probabilidade aumentada de desenvolver EM. [11][12][13][14][15][16][17][18][19] O número cumulativo de novas lesões em T2 também contribui para o aumento desse risco. 11,20 Além do número, também foi demonstrado que a localização das lesões pode prever a conversão de SCI em EM.…”
Section: Técnicas Convencionais De Ressonância Magnéticaunclassified
“…Em dois estudos retrospetivos, a presença de três ou mais lesões periventriculares foi considerado um preditor independente de desenvolvimento de EM. 15,18 Um deles incluiu 106 doentes com SCI com atingimento da medula espinhal. 15 Noutro estudo, que incluiu apenas doentes com nevrite ótica, a presença de lesões periventriculares, independentemente do número, aumentou significativamente o risco de EM.…”
Section: Técnicas Convencionais De Ressonância Magnéticaunclassified
See 1 more Smart Citation